Perencanaan Strategi Pemasaran Adaptif Pada UMKM Mustikasari Menggunakan Pendekatan Value Proposition Canvas (VPC) dan Business Model Canvas (BMC) - Rachel Sifa; Hilmi Aulawi; Rina Kurniawati (Institut Teknologi Garut, 2026)
MSMEs are business activities carried out by individuals or small groups, which are currently experiencing significant growth. This study aims to design an adaptive marketing strategy for Mustikasari MSMEs by combining the Value Proposition Canvas (VPC) and Business Model Canvas (BMC) approaches. VPC is used to identify the value expected by customers with the value offered by Mustikasari MSMEs. Meanwhile, BMC provides a complete picture of the Mustikasari MSME business model. Based on the analysis results, it shows that customers prioritize taste quality, product variety, and ease of ordering products. However, Mustikasari MSMEs also face weaknesses in their digital promotion system and distribution channels, which are still focused on physical stores only. The proposed adaptive marketing strategy includes increasing digital promotion through social media, developing sales channels through marketplaces, developing new variants in line with current trends, and strengthening local partnerships. Combining the VPC and BMC approaches provides a solution for Mustikasari MSMEs in designing an adaptive marketing strategy that is responsive to market changes and customer needs. Additionally, the results of this study are also expected to contribute to enhancing the competitiveness of MSMEs in the current digital era through structured and digital-based marketing strategies.